Penerapan TAM untuk Meningkatkan Adopsi Cloud Kitchen oleh UMKM Jabodetabek - Anung Titra Kurnia; Ringkar Situmorang; Krist Ade Sudiyono (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the factors influencing the adoption of cloud kitchen technology by micro, small, and medium enterprises (MSMEs) in the Greater Jakarta area (Jabodetabek) using the Technology Acceptance Model (TAM). The focus is on understanding the roles of perceived usefulness, ease of use, perceived benefits, value, risk, and technological knowledge in shaping adoption decisions. Methodology/approach: This research employs a quantitative approach through structured surveys distributed to MSME owners in Jabodetabek. The survey assessed TAM-based variables, such as perceived usefulness and ease of use, along with contextual variables, including perceived benefit, perceived value, perceived risk, and knowledge of technology. Results/findings: The findings reveal that perceived usefulness and perceived ease of use significantly affect MSMEs’ willingness to adopt cloud kitchen technology. These perceptions are shaped by enterprises' level of technological knowledge, assessment of benefits and value, and risk perception. Cloud kitchens are perceived to offer operational efficiency, lower overhead costs, and broader distribution channels, making them attractive options for MSMEs in competitive markets. Conclusion: MSMEs’ understanding and perception of cloud kitchens’ ease of use and practical benefits significantly influence their adoption. Increasing digital literacy is key to accelerating adoption. Limitations: This study is limited to MSMEs in Jabodetabek, which may restrict the applicability of the results to other regions or business environments. Contribution: This study provides strategic insights for MSMEs, policymakers, and technology developers to support digital transformation in the food service industry.